Esperanza rising - Ryan, Pam Muñoz (New York Scholastic, 2000)
When Esperanza and Mama are forced to flee to the bountiful region of Aguascalientes, Mexico, to a Mexican farm labor camp in California, they must adjust to a life without fancy dresses and servants they were accustomed to on Rancho de las Rosas. Now they must confront the challenges of hard work, acceptance by their own people, and economic difficulties brought on by the Great Depression. When Mama falls ill and a strike for better working conditions threatens to uproot their new life, Esperanza must relinquish her hold on the past learn to embrace a future ripe with the riches of family and community.--Provided by publisher.
Keywords: Mexican Americans -- California -- Juvenile fiction; Mexican Americans -- California -- Fiction; Agricultural laborers -- Fiction; California -- Fiction